2019
DOI: 10.1080/1828051x.2019.1610338
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac transcriptome study of the effect of heat stress in yellow-feather broilers

Abstract: The yellow-feather broiler is a popular poultry breed in Asia, particularly in China. In this study, we performed RNA-seq analysis to identify differentially expressed genes (DEGs) in the heart of yellow-feather broilers that had been subjected to heat stress treatment (38 ± 1 C for 8 h, over 7 d) and determine the response of the heart to high temperature and its effects on yellowfeather broiler physiology. We found that body weight (BW) of the heat stress treatment group (BW 28 ¼ 354.8 ± 34.8 g) was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…In poultry, relative weights of tissue are usually assessed as indicators of physiological development ( Van et al, 2013). Previous studies have shown that the heat stress-driven decline in the growth performance of fast-growing broilers has varying effects on organs, including the relative weight reduction of the spleen, thymus, bursa, and heart (Quinteirofilho et al, 2010;Zhang et al, 2017), but no significant difference in relative heart weight was found in slow-growing chickens and YFC under chronic heat stress (Zhang et al, 2017;Zhang et al, 2019). In the present study, the authors found that HWI was not affected significantly by chronic heat stress, and they observed normal physiological development of the liver in the treatment group YFC ( Van et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In poultry, relative weights of tissue are usually assessed as indicators of physiological development ( Van et al, 2013). Previous studies have shown that the heat stress-driven decline in the growth performance of fast-growing broilers has varying effects on organs, including the relative weight reduction of the spleen, thymus, bursa, and heart (Quinteirofilho et al, 2010;Zhang et al, 2017), but no significant difference in relative heart weight was found in slow-growing chickens and YFC under chronic heat stress (Zhang et al, 2017;Zhang et al, 2019). In the present study, the authors found that HWI was not affected significantly by chronic heat stress, and they observed normal physiological development of the liver in the treatment group YFC ( Van et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The control group was kept at 25 ± 1 °C, 24 hours a day. Bodyweight (BW) and cloacal temperature (CT) were measured according to (Zhang et al, 2020;Zhang et al, 2019). All 28-day-old YFC from the treatment and control groups were euthanized at the end of the final day of the heat stress treatment, and their livers were removed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations